Influence of Donor‐Acceptor Interactions on MLCT Hole Reconfiguration in {Ru(bpy)} Chromophores - Cotic, Agustina Ludmila (2024)
In MLCT chromophores, internal conversion (IC) in the form of hole reconfiguration pathways (HR) is a major source of dissipation of the absorbed photon energy. Therefore, it is desirable to minimize their impact in energy conversion schemes by slowing them down. According to previous findings on {Ru(bpy)} chromophores, donor-acceptor interactions between the Ru ion and the ligand scaffold might allow to control HR/IC rates. Here, a series of [Ru(tpm)(bpy)(R-py)]2+ chromophores, where tpm is tris(1-pyrazolyl)methane, bpy is 2,2’-bipyridine and R-py is a 4-substituted pyridine, were prepared and fully characterized employing electrochemistry, spectroelectrochemistry, steady-state absorption/emission spectroscopy and electronic structure computations based on DFT/TD-DFT. Their excited-state decay was monitored using nanosecond and femtosecond transient absorption spectroscopy. HR/IC lifetimes as slow as 568 ps were obtained in DMSO at room temperature, twice as slow as in the reference species [Ru(tpm)(bpy)(NCS)]+.